PENGARUH SEKAM PADI BAKAR TERHADAP PERTUMBUHAN BIBIT BATANG BAWAH KARET KLON PB 260 (Hevea brasiliensis Muell Arg.) - fatehahwati, fatehahwati; Sopiana, Sopiana; fitry ramanda, Rika (Journal of Agro Plantation (JAP), 2023)
Rubber plant (Hevea brasiliensis Muell Arg.) is one of the important plantation commodities for Indonesia because it is one of Indonesia's export commodities for foreign exchange. The problem in rubber nurseries today is the limitation of fertile soil as a planting medium in polybags. Efforts to overcome this problem are to utilize mineral soils that lack nutrients such as alluvial subsoil by giving roasted rice husks. Roasted rice husks contain 35.98% organic C and macronutrients such as N (0.73%), P (0.14%) and K (0.3%). This research was carried out from October 2021 to January 2022 at the Ketapang State Polytechnic Experimental Garden. This study used a non-factorial Completely Randomized Design (CRD) with 6 treatments and 4 replications, so there were 24 experimental units. Each replication consisted of 3 plant samples so that 72 samples were obtained. Observation parameters included plant height (cm), stem circumference (cm), number of umbrellas (strands), plant wet weight (g), and plant dry weight (g). The data obtained were analyzed by means of variance with Analysis of Variance (ANOVA). The best dose of roasted rice husk on the growth of rubber rootstock seedlings of clone PB 260 was 90 g/plant.